Pengaruh Workplace Sprituality dan Budaya Organisasi Terhadap Work Engagement pada UPT Balai Monitor Spektrum Frekuensi Radio Kelas I Pekanbaru - Amanda Putri; Ade Ria Nirmala (Yayasan Almanar Pujud, 2025)
UPT Pekanbaru Class I Radio Frequency Spectrum Monitoring Center is a technical implementation unit under the Directorate General of SDPPI which is tasked with monitoring and controlling frequencies in the Riau region. This research aims to analyze the influence of workplace spirituality and organizational culture on work engagement. The method used is quantitative with a survey approach, using a questionnaire distributed to 47 employees using a purposive sampling technique. Data were analyzed using SPSS. The research results show that Workplace Spirituality has a significant effect on Work Engagement, while organizational culture does not have a significant effect on Work Engagement. Simultaneously, these two independent variables influence work engagement. These findings emphasize the importance of paying attention to organizational culture and the potential impact of Workplace Spirituality conflict in relation to employee work engagement.